CL57BL/6 마우스의 발모에 미치는 목향 추출물의 영향 - 김정희; Joung-hee Kim; 이승욱; Syng-ook Lee; 백경연; Gyoung Yeun Beik; 김극준; Keuk-jun Kim (Korean journal of clinical laboratory science, 2021)
본 연구에서는 제모된 마우스 모델을 대상으로 목향 추출물의 경구 투여가 발모에 미치는 영향에 대해 조사하였다. 목향 70% prethanol 추출물(ALD)을 제조하여 추출수율과 추출물에 함유된 총 폴리페놀 함량을 측정한 결과 각각 27.30±0.01과 28.39 mg gallic acid equivalent (GAE)/g extract로 측정되었다. ALD를 제모된 CL57BL/6 마우스에 6주간 경구 투여하며 관찰한 결과, 식이량과 체중 변화에 유의적인 변화가 관찰되지 않았다. 혈액 생화학적 검사 및 조직학적 검사를 통해 ALD의 6주간 반복 투여가 주요 장기인 간과 신장의 기능에 미치는 영향을 살펴본 결과, 대조군에 비해 간기능과 콩팥기능 모두 유의적인 변화는 관찰되지 않았다. 이와 더불어 ALD 투여에 따른 모발 성장 정도를 육안적으로 관찰한 결과, ALD 투여군에서 대조군 및 판시딜 투여군(양성 대조군)보다 현저하게 발모가 증가함을 확인하였다. 또한 모낭수와 진피의 콜라겐 생성 정도를 비교한 결과, 대조군 및 판시딜 투여군 대비 ALD 투여군에서 두 항목 모두 유의적으로 증가함을 알 수 있었다. 본 연구로부터 ALD의 경구 투여는 제모된 마우스 모델에서 모발 성장을 촉진하며 진피내 콜라겐 합성 증가와 모낭수 증가를 유도한다는 결론을 도출할 수 있었으며, 이는 ALD를 함유하는 경구용 발모 촉진제 개발을 위한 기초자료로써 그 가치가 있을 것으로 기대된다. Aucklandia lappa Decne., a traditional herbal medicine, has been used to treat various diseases, including asthma, coughs, rheumatism, and diarrhea. In the present study, the effects of the oral administration of Aucklandia lappa Decne. extract on hair growth was investigated in hair-removed mice. A 70% ethanol extract of Aucklandia lappa Decne. (ALD) was prepared, and the extraction yield and total polyphenol content of ALD were measured as 27.30±0.01 and 28.39 mg gallic acid equivalent (GAE)/g, respectively. The oral administration of ALD to hair-removed CL57BL/6 mice for six weeks had no significant effects on food intake and body weight changes. Biochemical and histological examinations also showed that the oral administration of ALD for six weeks had no significant effect on the liver and kidney functions. On the other hand, hair growth was significantly higher in the ALD group than the control group and the Pancidil group (positive control). In addition, the number of hair follicles and the degree of collagen production in the dermis were significantly higher in the ALD group than in the control and pancidil groups. These results suggest that ALD is a potential source of nutricosmetics with hair growth-promoting effects. Copyright Ⓒ 2021 The Korean Society for Clinical Laboratory Science. All rights reserved.